A reconfiguration approach for a supply chain tracking platform. (26th January 2022) - Zidi, Hedi; Hamani, Nadia; Laajili, Cyrine; Benaissa, Mounir
Over the last few years, companies have resorted to the implementation of reconfigurable supply chain that are able to deal with the market expectation and the client's needs, whatever the conditions, by adopting new technologies characterising the fourth industrial revolution such as internet of things and cloud computing. Moreover, the emergence of these new technologies imports solutions for more efficient shipping, real-time tracking and traceability. These solutions have made logistic entities more connected, intelligent, autonomous, reconfigurable and even capable of acting at the real time. Inspired by these new technologies, several researchers have described in their works, how useful they are, especially to design and model digital platform for real-time transport tracking. In order to design a reconfigurable supply chain, we extended a collaborative platform to introduce reconfiguration mechanisms in order to make it reactive whatever the event type is. We used Unified Modelling Language to model and design reconfiguration mechanisms.